2018
DOI: 10.1016/j.neuropharm.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Selective HCN1 block as a strategy to control oxaliplatin-induced neuropathy

Abstract: a b s t r a c tChemotherapy-Induced Peripheral Neuropathy (CIPN) is the most frequent adverse effect of pharmacological cancer treatments. The occurrence of neuropathy prevents the administration of fully-effective drug regimen, affects negatively the quality of life of patients, and may lead to therapy discontinuation. CIPN is currently treated with anticonvulsants, antidepressants, opioids and non-opioid analgesics, all of which are flawed by insufficient anti-hyperalgesic efficacy or addictive potential. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 45 publications
2
58
0
Order By: Relevance
“…As HCN2, HCN3, or mixed HCN2 + HCN3 channels are functionally expressed in GH 3 cells [24], OXAL-induced stimulation of I h in native cells does not tend to be isoform specific, although our experimental results showed that OXAL could modify the amplitude and gating of I h in GH 3 and R1220 cells. Because of the importance of I h (i.e., HCNx-encoded currents) in contributing to excitability and automaticity of electrically excitable cells [18,22,28,38,40,50], findings from the present results could provide novel insights into electrophysiological and pharmacological properties of OXAL or other structurally related compounds [19,20].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As HCN2, HCN3, or mixed HCN2 + HCN3 channels are functionally expressed in GH 3 cells [24], OXAL-induced stimulation of I h in native cells does not tend to be isoform specific, although our experimental results showed that OXAL could modify the amplitude and gating of I h in GH 3 and R1220 cells. Because of the importance of I h (i.e., HCNx-encoded currents) in contributing to excitability and automaticity of electrically excitable cells [18,22,28,38,40,50], findings from the present results could provide novel insights into electrophysiological and pharmacological properties of OXAL or other structurally related compounds [19,20].…”
Section: Discussionmentioning
confidence: 86%
“…For example, OXAL has been demonstrated to suppress different types of voltage-gated K + or Na + currents in various preparations, such as myelinated axons, sciatic-nerve preparations, and motoneuron-like cells [11,[13][14][15][16]. Of interest, this agent was also recently reported to activate I h in isolated dorsal root ganglion neurons, and this action is thought to be implicated in its modifications of pain sensation [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is also necessary to point out that the potential of HCN blockers in cardiac pathologies and in the management of pain is well established and that the compounds able to increase I h (e.g., oxaliplatin) may have the therapeutic potential [42,43]. Caution thus entails being raised in attributing the action of CIL on either cardiac function or neuronal networks widely to the block of I h [2,18,19,30,[34][35][36]44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In the next set of experiments, we examined and compared the effects of croton-03, YS-035, zatebradine, croton-03 plus SQ-22536, and croton-03 plus oxaliplatin on I h amplitude in GH 3 cells. YS-035 or zatebradine was recognized as an inhibitor of I h [19,29], oxaliplatin was recently demonstrated to stimulate I h [30,31], and SQ-22536 is an inhibitor adenylate cyclase. As illustrated in Figure 4, similar to the effect of croton-03 on I h described above, the addition of either YS-053 (3 µM) or zatebradine (3 µM) was effective at depressing I h amplitude.…”
Section: Effect Of Croton-03 Ys-035 Zatebradine Croton-03 Plus Sq-mentioning
confidence: 99%